2018
DOI: 10.21432/cjlt27572
|View full text |Cite
|
Sign up to set email alerts
|

Learning with Multiple Representations: Infographics as Cognitive Tools for Authentic Learning in Science Literacy | Apprendre avec des représentations multiples: l'infographie de presse comme outil cognitif pour l'apprentissage authentique en science

Abstract: This paper presents a descriptive case study where infographics—visual representation of data and ideas—have been used as cognitive tools to facilitate learning with multiple representations in the context of secondary school students’ science news reporting. Despite the complementary nature of the two research foci, studies on cognitive tools and multiple representations have evolved independently. This is because research on cognitive tools has narrowly focused on technological artifacts and their impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 47 publications
(69 reference statements)
0
12
0
1
Order By: Relevance
“…Additional support for using visual documents in social studies classrooms can be found within research of multimodal learning, which has consistently suggested that visual elements often enhance learners' comprehension, retention and transfer of information (Gebre, 2018;Mayer, 2008Mayer, , 2017Mayer et al, 2003). Presenting students with information formatted in both pictures and words tends to be more powerful than presenting words alone, due, in part, to the potential for learners to synthesize multimedia data (Mayer, 2008(Mayer, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Additional support for using visual documents in social studies classrooms can be found within research of multimodal learning, which has consistently suggested that visual elements often enhance learners' comprehension, retention and transfer of information (Gebre, 2018;Mayer, 2008Mayer, , 2017Mayer et al, 2003). Presenting students with information formatted in both pictures and words tends to be more powerful than presenting words alone, due, in part, to the potential for learners to synthesize multimedia data (Mayer, 2008(Mayer, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple representations is an approach that refers to the use of different visual tools, texts, and diagrams and means data and ideas that illustrate phenomena in science learning. Several scientists have proposed multiple representation learning to apply infographicbased instruction in various disciplines for thorough student understanding (Gebre, 2018;Zheng et al, 2020).…”
Section: Multiple Representation Approach Learning Conceptmentioning
confidence: 99%
“…Infographic instruction has been implemented in recent years, often in science courses at the middle school, high school, or university level (Davidson, 2014;Fowler, 2015;Gebre, 2018;Lamb et al, 2014;Saunders, Horrell, & Murray, 2018). Additional scholarship includes infographic comprehension and composition within a ninth-grade social studies class studying migration (Staurseth & Haland, 2019) and language arts students making connections between To Kill a Mockingbird and contemporary social justice issues (Yearta et al, 2018).…”
Section: Infographic Instructionmentioning
confidence: 99%
“…Teachers and students can consider what they want to communicate, the kind of infographic that makes sense given the data or information, and any design elements that might be included. Gebre (2018) noted that "creating an infographic is a knowledge construction process" (p. 16). Thus, it is essential for a teacher to model the thought process that goes into creating an infographic, as there are many decisions that need to be made.…”
Section: Infographic Creationmentioning
confidence: 99%